The method of improving intonation for violinests and violists students in faculty of music UiTM Shah Alam / Melvin David - David, Melvin (2013)
The method of improving intonation for violinists and violists students in Faculty of Music, UiTM Shah Alam is a study to find the causes of intonation problem and to find the methods to improve intonation in violin and viola playing. The study was conducted at the Faculty of Music, UiTM Shah Alam, among the undergraduate students in the faculty. The data of the study was collected through the distribution of questionnaires with the use of qualitative method.